0782 The Modified Epworth Sleepiness Scale Predicts Hypersomnia but not Obstructive Sleep Apnea in a Pediatric Population. (27th April 2018) - Goldman, L; Rossi, G; Burkhead, C; Relia, S; Dayyat, E A
Abstract: Introduction: The Epworth Sleepiness Scale is a validated questionnaire used by many physicians to assess daytime sleepiness in patients. The Modified Epworth Sleepiness Scale (mESS) is used in children. Our study aims to assess the utility of the mESS in identifying obstructive sleep apnea (OSA) and hypersomnia in children. Methods: We performed a retrospective chart review collecting data from patients who attended our pediatric sleep clinic in 2015 and 2016 who completed both a mESS and Polysomnography (PSG), with or without Mean Sleep Latency Test (MSLT). We collected data points including scores on individual questions within the mESS, total mESS score, body-mass index (BMI), Apnea-Hypopnea Index (AHI), mean sleep latency (MSL) and sleep-onset REM (SOREM). Data was assessed using various statistical analyses. Results: 158 patients (56.3% male) between 6–19 years old (12.6 ± 3.27), majority were African American (73.4%), White (22.2%), and other racial backgrounds (4.3%). Average participant's BMI (30.36 ± 10.4). Total mESS scores significantly correlated with MSL (r= -.302, p<.005), whereas total mESS did not significantly correlate with AHI, but did approach statistical significance (r = -.155, p = .052). Cronbach's Alpha score, a measure of internal consistency, for the 8-question mESS was α = .796. This value decreased when any of the questions was removed. BMI was able to predict 12% of variance in AHI, but reached to 14% when BMI was combined with mESS. Conclusion: The mESS is a reliable screening tool for hypersomnia, but it has limited use in isolation for predicting OSA in children. The mESS is able to accurately predict abnormal MSL, but it does not predict AHI. This may be due to the difference in phenotypic manifestations of sleep-disordered breathing in children presenting with neurocognitive deficits, compared to adults who will suffer from neurocognitive impairment but usually complain of sleepiness. The mESS is most reliable when its integrity is maintained. Only when it is considered in conjunction with other predictor variables does it add predictive value for pediatric OSA. Support (If Any): None.